Influence of Financial Performance on Financial Distress with Company Value as an Intervening Variable: Empirical Study of Construction Companies Listed on the Indonesian Stock Exchange 2020-2022 - Sitepu, Latresia Aprilia BR; Yuliusman, Yuliusman; Kusumastuti, Ratih (PT. Riset Press International, 2024)
This research aims to determine the effect of financial performance on financial distress with company value as an intervening variable in construction companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples in this research was 19 companies with an observation period of 3 years so the total research sample was 57. The results of this research show that: (1) Financial performance has a positive and significant effect on company value. (2) Financial performance has a positive and significant effect on financial distress. (3) Company value has a negative and insignificant effect on financial distress. (4) Financial performance has a negative and insignificant effect on financial distress with company value as an intervening variable.